Pengembangan Gerak Uncul sebagai Dasar Penciptaan Karya Tari “Aer Sengketa” - Mega Suryanti; Deden Haerudin; B. Kristiono Soewardjo (Jurnal Pendidikan Tari, 2023)
The dance piece entitled Aer Sengketa comes from the Ujungan Arts tradition. Where Ujungan art is interpreted as a form of legitimacy of gratitude for the successful rice harvest and strengthens friendship between fighters from various directions. Accompanied by sampyong music as an accompaniment to the Uncul dance during the Ujungan game, combined with mask music, the atmosphere is more dramatic. This dance style has a number of dancers that will be used, namely 8 dancers, 10 silat players, 8 uncul dancers and 2 bobotoh. The purpose of creating the dance is to represent the culture of the Betawi people in the form of gratitude for the success of the rice harvest and to strengthen ties between fighters in various directions. The dance creation method uses Moving From Within from Alma M. Hawkins' book entitled “Moving From Within: A Method For Dance Making” which was translated by I Wayan Dibia into “Moving According to Your Heart”. The results of the creation of the Aer Sengketa dance enriched the motion motifs of the Betawi dance styles, as follows Gibang, Kewer, Goyang Plastik, Goyang Cendol, Slancar, and also silo tiger and mincit silat movements.